Corporate Social and Environmental Responsibility (CSER) Reporting Practices in a Developing Country: Evidence from Bangladesh - Hossain, MD Moazzem (Curtin University, 2014)
This study explores CSER reporting phenomenon in Bangladesh. Constructivist ontology and interpretivist epistemology research methodology was used. Findings from this engagement-based study reveal the underpinning assumptions of CSER regarding enablers and barriers, stakeholders’ expectations and suggested strategies. Findings and the social system-based theories resonate well with the literature providing theoretical and practical contributions to the body of knowledge. This study provides valuable insights for scholars, policy makers, managers and organisations.